Low total physical activity, high total sitting time and high sitting time on a work day are correlated with low fitness in male working adults: a cross sectional study - Wibowo, Rakhmat Ari; Wasityastuti, Widya; Sofro, Zaenal Muttaqien (Bangladesh Journal of Medical Science, 2019)
Background : Low fitness is an emerging factor for cardiovascular diseases. Physical activity and sitting time are arising factors that influence fitness level. There are some debates on what domain of physical activity and sitting time that have more influences on fitness level. The aims of this study were to (1) explore each domain of physical activity & sitting time and analyze their associations with low fitness in male working adults and (2) explore the differences between sitting time on a working day and a day-off. Method :In this cross-sectional study, a total of 31 healthy male staffs were recruited. Participants used International Physical Activity Questionnaire (IPAQ) long version to recall their physical activity and sitting time, and their fitness level was measured by a submaximal exercise test. Data were analyzed both by univariate and multivariate techniques. Multivariable logistic regressions were employed to calculate Odds Ratio (OR) of low fitness by each domain of physical activity and sitting time. Result : Data of 27 participants were considered for analysis. Total physical activity was inversely associated with low fitness [OR 0.961, 95% Confidence Interval (95% CI) 0.928 – 0.995]. Total sitting time and sitting time on a working day were positively associated with low fitness (total sitting time: OR 1.101, 95% CI 1.001-1.211; sitting time on a working day: OR 1.01, 95% CI 1.001-1.019). We also observed that sitting on a working day was significantly higher than sitting time on a day-off (p = 0.004). Conclusion : The results support association of total physical activity, total sitting time and sitting time on a working day with fitness level. There were also difference between sitting time on a working day and a day-off. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.279-287